(untitled) (Heritage, 2023)
Domicide, а term that recently emerged in the field of geography, has been further revised in contemporary studies to include various processes concerning housing issues in life-endangering situations. These elaborations questioned the basis of the concept that aimed to explain the planned physical destruction of homes by revising its compositional notions and its typology. This article provides an overview of some of the most relevant studies in the given domain by assessing the applicability of the term in anthropological research. It starts from the premise that the trope of the victimhood prevents its usage in anthropology, while simultaneously mapping multidisciplinary approaches that widen the span of domicide in accordance with an anthropological framework. Offered explanations are briefly complemented with observations acquired during fieldwork on internally displaced persons from Kosovo and Metohija.